On the Role of the Environments and Star Formation for Quasar Activity - Bettoni, Daniela; Falomo, Renato; Kotilainen, Jari K.; Karhunen, Kalle (Frontiers in Astronomy and Space Sciences, 2017)
We investigate the host galaxy and environment properties of a sample of 400 low z ($<$0.5) quasars that were imaged in the SDSS Stripe82. We can detect and study the properties of the host galaxy for more than 3/4 of the whole data set. We found that quasar hosts are dominated by luminous galaxies of absolute magnitude $M_* -3 < M(R) < M_*$ and that the galaxy number density of the quasar environments is comparable to that of the inactive galaxies with similar luminosities. For these quasars we undertake also a study in u,g,r,i and z SDSS bands and again we found that the mean colours of the quasar host galaxy are very similar to the values of the sample of inactive galaxies. For a subsample of low z sources the imaging study is complemented by spectroscopy of quasar hosts and of close companion galaxies. This study suggests that the fueling and triggering of the nuclear activity is only weakly dependent on the local environment of quasars. Contrary to past suggestions, for low redshift quasar there is a very modest connection between recent star formation and the nuclear activity.